Correlation of tobacco smoke exposure to intelligence quotient in preschool children - Nina Natalia; Nurhayati Masloman; Jeanette C. Manoppo (Paediatrica Indonesiana, 2012)
Background Exposure to tobacco smoke at home happens in 29-69% of children globally and 43% oflndonesian children. Smokeexposure during the developmental stage may affect cognitiveabilities, as measured by intelligence quotient (IQ). There havebeen few studies conducted on the correlation of tobacco smokeexposure to IQ. This is the first study of this type in Indonesia.Objectives To assess the correlation between tobacco smokeexposure and IQ in preschool children and to assess the correlationbetween serum cotinine levels and IQ in preschool childrenexposed to tobacco smoke.Methods A cross-sectional study was conducted in the Tumintingdistrict, Manado in January - May 2011. Subjects were collected byrandom sampling of 3-5 year-old children. In our study, 35 childrenwere deemed to have been exposed to tobacco smoke by serumcotinine ~ 0.05 ng/ml and 25 children were deemed to not havebeen exposed to tobacco smoke (cotinine < 0.05 ng/ml). Resultswere analyzed by t-test and simple correlation analysis using SPSSversion 17 software with a significance level of P < 0.05.Results There was a statistically significant difference in IQbetween the two groups, with mean IQ of 106.54 in the groupexposed to tobacco smoke and mean IQ of 109.36 in the group notexposed to tobacco smoke (P=0.01). The mean serum cotininelevel in the group with tobacco smoke exposure was 1. 77 ng/mL.There was no correlation between the mean level of cotinine andmean IQ in this group (r = -0.19 and P=0.14).Conclusions The mean IQ in the group with tobacco smokeexposure was lower than that of the group not exposed to tobaccosmoke. There was no correlation between mean serum cotininelevel and mean IQ. [Paediatr lndones. 2012;52: 106-10].